Peripheral Blood Based Discrimination of Ulcerative Colitis and Crohn's Disease from Non-IBD Colitis by Genome-Wide Gene Expression Profiling. Issue 1 (29th May 2013) - Sipos, Ferenc; Galamb, Orsolya; Wichmann, Barnabás; Krenács, Tibor; Tóth, Kinga; Leiszter, Katalin; Műzes, Györgyi; Zágoni, Tamás; Tulassay, Zsolt; Molnár, Béla
Abstract : A molecular diagnostic assay using easily accessible peripheral blood would greatly assist in the screening and diagnosis of ulcerative colitis (UC) and Crohn's disease (CD). Transcriptional profiles in blood/biopsy samples from 12 UC (6/12), 9 CD (5/9), 6 non-inflammatory bowel disease (non-IBD) colitis (6/0), and 11 healthy (11/11) patients were assessed by Affymetrix HGU133Plus2.0 microarrays. Prediction analysis of microarrays, discriminant and ROC analyses were performed, the results were validated by RT-PCR and immunohistochemistry using also an independent set of samples (15 blood samples, 45 biopsies). A set of 13 transcripts was differentially expressed in IBD, non-IBD controls and healthy blood samples (100% specificity and sensitivity). Validated difference was found in 16 transcripts between UC, non-IBD and normal blood, and 4 transcripts between CD, non-IBD and normal samples. UC and CD blood cases could be also distinguished by 5 genes with 100% specificity and sensitivity. Some disease associated alterations in blood transcripts were also detected in colonic tissue. IBD subtypes may be discriminated from non-IBD (diverticulitis, infective and ischemic colitis) in vitro from peripheral blood by screening for differential gene expression revealed in this study. Transcriptional profile alterations in peripheral blood can be located in diseased colon.